Keandalan dalam Memberikan Pelayanan Restaurant terhadap Revisit Guest Studi pada Food and Beverage Service di Narendra Restaurant - Asmara, Denny (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2022)
The Food and Beverage Service Department is responsible for meeting the food and drink needs of its guests. In carrying out operational activities, employees of the Food and Beverage Service Department must have knowledge of how to serve food and drink properly. The purpose of the study was to determine the quality of food & beverage service. Methods Data collection techniques using interviews, observations, literature studies, documentation, and qualitative descriptive methods. The results in this study are the quality of service provided by the Food and Beverage Department at The Sunan Hotel Solo is classified as good and includes several aspects, namely tangible, reliability, responsiveness, empathy, assurance as evidenced by guests who make recommendations and repeat guests. From the elaboration of the results of the discussion that has been described above, it can be concluded that the quality of service provided by the Food & Beverage staff at The Sunan Hotel Solo is quite good, resulting in guest satisfaction.